2019
DOI: 10.1136/bmj.l298
|View full text |Cite
|
Sign up to set email alerts
|

Serious adverse events and lifetime risk of reoperation after elective shoulder replacement: population based cohort study using hospital episode statistics for England

Abstract: ObjectivesTo provide accurate risk estimates of serious adverse events after elective shoulder replacement surgery for arthritis, including age and sex specific estimates of the lifetime risk of revision surgery.DesignPopulation based cohort study.SettingHospital episode statistics for NHS England, including civil registration mortality data.Participants58 054 elective shoulder replacements in 51 895 adults (aged ≥50 years) between April 1998 and April 2017.Main outcome measuresThe lifetime risk of revision su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 32 publications
3
44
0
Order By: Relevance
“… 1 , 2 , 28 However, as previous studies comparing surgical practices in England for upper limb conditions have shown a lower intervention rate, we consider this difference to reflect changes in clinical practice in England in comparison to other countries, rather than incomplete data capture. 29 , 30 , 31 Carpal tunnel decompression surgery was more common in women than men, especially among women in the perimenopausal age range. Longitudinal follow-up within this dataset enabled us to calculate overall serious complication rates, which show that carpal tunnel decompression is usually a safe operation.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 28 However, as previous studies comparing surgical practices in England for upper limb conditions have shown a lower intervention rate, we consider this difference to reflect changes in clinical practice in England in comparison to other countries, rather than incomplete data capture. 29 , 30 , 31 Carpal tunnel decompression surgery was more common in women than men, especially among women in the perimenopausal age range. Longitudinal follow-up within this dataset enabled us to calculate overall serious complication rates, which show that carpal tunnel decompression is usually a safe operation.…”
Section: Discussionmentioning
confidence: 99%
“…Other commonly used cohorts consist of administrative or claim data on the hospital, regional, or national level. [29][30][31][32] To our knowledge, the present cohort is unique within the field of hand and wrist disorders because it contains a large number of patients with relatively detailed data, covering both outcomes, treatment information, and patient characteristics. A limitation, however, is that this cohort is not representative of all hand and wrist patients in The Netherlands, for example, because complex trauma patients and patients with more severe comorbidities may be treated more often elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“… 16 This trend is not unique to the United States, as England saw an even larger 5.6-fold increase in TSA volume between 1998 and 2017. 14 The use of TSA is expected to continue to rise, driven by an increasing prevalence of shoulder pathology and expanding operative indications in an aging population. 12 …”
mentioning
confidence: 99%